Type I osteogenesis imperfecta: a case report - Guach Hevia, David Armando; Almira Gómez, Carlos Rafael (Correo Científico Médico, 2022)
The term osteogenesis imperfecta includes several genetic defects of type I collagen, clinically traduced in bone fragility and deformity. The type I or Lobstein variety is the most frequent form of the disease and is characterized by a pattern of autosomal dominant inheritance. The case of a 65-year-old female patient, who came to our medical service at “Lucia Iñiguez Landin” Hospital of Holguin, Cuba, with multiple fractures after a slight fall was reported. She had short stature, a history of multiple fractures along her life, joint hypermobility, and blue grayish bulbar conjunctiva. Given the positive family history and the phenotypic assessment of the clinical picture, the patient was diagnosed with type I osteogenesis imperfecta. A detailed evaluation was carried out and the available medication was prescribed. The diagnostic and therapeutic update on this disease in Cuba is crucial for enhancing life quality of those who are affected. Keywords: osteogenesis imperfecta, bone fragility and deformity, multiple fractures, diagnostic and therapeutic update